(untitled) (Khairulummah, 2023)
The last 23 years of Prophet Muhammad’s (PBUH) life, in which he fulfilled his Prophet Hood, especially in Makkah, was full of patience and suffering. During this period, difficulties and problems came up one after another, which the Prophet (PBUH) faced with courage and strategy. Because Allah Ta’ala chose him as his last Prophet and made Him an example for the whole world. That is why trials also became a part of His life. The difficult stages He had to go through while carrying out his Prophet Hood, none of the previous Prophets had experienced so much. For this reason, He was also blessed with the title of Rahmat al-Alamin. The Farewell Sermon in a very important way highlights the fact that Prophet Muhammad (PBUH) is the first blessed person in the fourteen hundred years of history who brought a broad and comprehensive message to all humanity and turned this message into a movement. Issued in the form and established an Islamic state on it and to convey it to all the nations of the world, established a group of martyrs (O people! Be witnesses) through which the sayings of the Holy Prophet (PBUH) on the occasion of the farewell Hajj. But it was said that they reached us. Keywords: A Research Study, The Eloquence, The Sermon, Farewell.